Biochemical changes in myofibrillar and sarcoplasmatic meat proteins at different freezing rates - Bodiroga, Biljana; Vasiljević, Ljubica; Vujadinović, Dragan; Savanović, Danica; Tomović, Vladimir (Journal of Engineering & Processing Management, 2019)
Freezing rate significantly affects the quality of frozen meat and its biochemical changes. The loss of water from the cellular structure, which, under normal conditions, acts as a mechanical barrier between protein chains, causes spontaneous interactions of proteins that result in their denaturation. In order to determine the content of myofibrillar and sarcoplasmic proteins in meat samples, the samples were frozen at rates of 0.40, 0.90, and 1.25 cm/h for a storage period of 15 days. Protein content was analyzed by capillary gel electrophoresis and high-pressure liquid chromatography. During the freezing process, the protein chains were found to be shortened so that myofibrillar proteins were between 20 and 50 kDa, whereas sarcoplasmic proteins were between 20 and 100 kDa at all the freezing rates mentioned. The results of the analysis also show that the total number of sarcoplasmic proteins (freezing rate 0.90 cm/h; 20 proteins) was lower than the total number of myofibrillar proteins (freezing rate 0.90 cm/h; 35 proteins), and the molecular weight for both types of protens was lower 50 kDa. Further research should be directed towards extending storage time.